1999
DOI: 10.1029/1999pa900044
|View full text |Cite
|
Sign up to set email alerts
|

Dansgaard‐Oeschger and Heinrich event imprints in Alboran Sea paleotemperatures

Abstract: Abstract. Past sea surface temperature (SST) evolution in the Alboran Sea (western Mediterranean) during the last 50,000 years has been inferred from the study of C37 alkenones in International Marine Global Change Studies MD952043 core. This record has a time resolution of~200 years allowing the study of millennial-scale and even shorter climatic changes. The observed SST curve displays characteristic sequences of extremely rapid warming and cooling events along the glacial period. Comparison of this Alboran … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

58
485
2
19

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 563 publications
(564 citation statements)
references
References 70 publications
58
485
2
19
Order By: Relevance
“…Our MIS 11c SST records of Site 975 were compared to the Holocene SST records from core MD95-2043 from the Alboran Sea ( Fig. 1; Table 1; Cacho et al, 1999).…”
Section: Odp Site 975mentioning
confidence: 99%
“…Our MIS 11c SST records of Site 975 were compared to the Holocene SST records from core MD95-2043 from the Alboran Sea ( Fig. 1; Table 1; Cacho et al, 1999).…”
Section: Odp Site 975mentioning
confidence: 99%
“…coastal estuaries (Boski et al, 2002, in press), and the Ebro delta (Somoza et al, 1998), which augment the number of environments. Marine drill core information from Gulf of Cadiz and Alboran Sea (Cacho et al, 1999(Cacho et al, , 2001Sánchez-Goñi et al, 2002) suggests a elose synchronism between the rapid elimate changes reported in the North Atlantic and those recorded in lower latitudes.…”
Section: E-mail Address: Rncnzc65 @Rnncncsices (E Zazo)mentioning
confidence: 99%
“…Much information comes from coastal sectors studied in previous papers (e.g., Zazo et al, 1994Zazo et al, , 1999aZazo et al, c, 2005Borja et al, 1999;Dabrio et al, 1999Dabrio et al, , 2000Goy et al, 1996Goy et al, , 2003Lario et al , 2000Lario et al , , 2002Luque, 2002;YIl et al, 2003), and from Doñana-Huelva (Rodrí-guez-Ramírez et al, 1996Ruiz et al, 2005;Cáceres et al, 2006). The paper also ineludes data from Portuguese (Bard et al, 2000); M39-008 (Cacho et al, 2001; MD95-2043 (Cacho et al, 1999(Cacho et al, , 2001Sánchez-Goñi et al, 2002);H-658 C (de Menocal et al, 2000). coastal estuaries (Boski et al, 2002, in press), and the Ebro delta (Somoza et al, 1998), which augment the number of environments.…”
Section: E-mail Address: Rncnzc65 @Rnncncsices (E Zazo)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cultures of these species showed that the proportion of di-and triunsaturated alkenones changed linearly with water temperature [5,6]. This finding and the ubiquity of C 37 -C 39 alkenones in recent and past marine sediments has led to the widespread use of the C 37 homologs for the estimation of sea surface temperatures in climate change studies [7][8][9][10]. This method has become, at present, a reference standard for the measurement of paleotemperatures in paleo-oceanography.…”
mentioning
confidence: 99%